The man with the golden arm - Preminger, Otto; Newman, Walter; Meltzer, Lewis; Sinatra, Frank, 1915-1998; Algren, Nelson, 1909-1981. ([New York] : Carlyle Productions Inc., 1955)
Frankie Machina, a criminal addicted to gambling and heroin, played superbly by Frank Sinatra, after spending a good season in prison, returns home to Chicago with his wife, Eleanor Parker, with the firm intention of leaving his past behind. criminal and recover from their addictions. But it will not be easy for him, since his old and undesirable friends will be waiting for him, who will try by all means, for him to return to his old habits.--
Based on the novel by Nelson Algren.
Frank Sinatra, Eleanor Parker, Kim Novak, Arnold Strang, Darren McGavin, Robert Strauss, John Conte, Doro Merande.
Music by Elmer Bernstein ; editor, Louis R. Loeffler ; director of photography, Sam Leavitt.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed June 16, 2022)
Keywords: Drug addicts -- Drama; Drummers (Musicians) -- Drama; Motion pictures; Crime films; Feature films; Fiction films; Streaming video